An elementary quantum network of entangled optical atomic clocks - Nichol, B (2022)
Demonstration of entanglement-enhanced frequency comparison of two optical atomic clocks based on the 674nm quadrupole transition of 88Sr+ ions, which are linked by a quantum-optical fibre link (≈2 m long). We show that the use of an entangled state reduces the measurement uncertainty by nearly √2 , the value expected for the Heisenberg Limit. Today's optical clocks are typically limited by dephasing of the probe laser; in this regime, we find that entanglement yields a factor 2 reduction in the measurement uncertainty compared to conventional correlation spectroscopy techniques. We demonstrate this enhancement for the measurement of a frequency shift applied to one of the clocks.